Long-term safety of Mometasone Furoate administered via a dry powder inhaler in children: Results of an open-label study comparing Mometasone Furoate with Beclomethasone Dipropionate in children with persistent asthma - Corren Jonathan; Leflein Jeffrey; Noonan Michael; Staudinger Heribert (BMC, 2009)
Abstract Background To assess the long-term pediatric safety of 2 doses of mometasone furoate administered via a dry powder inhaler (MF-DPI) for mild-to-moderate persistent asthma and compare them with that of beclomethasone dipropionate administered via a metered dose inhaler (BDP-MDI) in the treatment of persistent asthma. Both MF-DPI doses tested are twice the approved pediatric dosage of 100 μg once-daily (QD) for children aged 4-11 years. Methods Children (N = 233) aged 4-11 years were randomized to 52 weeks of treatment with MF-DPI 200 μg QD AM, MF-DPI 100 μg twice daily (BID), or BDP-MDI 168 μg BID. Patients had used inhaled corticosteroids (ICSs) daily for ≥ 30 days before the screening visit and were on stable ICS doses for ≥ 2 weeks before screening. The primary safety variable was the incidence of adverse events. Secondary safety variables were laboratory tests (including cortisol concentrations), vital signs, and physical examination. Results The incidence of adverse events was similar in all 3 treatment groups. The most frequently reported adverse event was upper respiratory tract infection, reported by 47%-49% of the MF-DPI-treated patients and 51% of the BPD-treated patients. Most adverse events were considered unrelated to study drug. The most frequently reported related adverse events were headache (MF-DPI 200 μg QD AM, 8%; MF-DPI 100 μg BID, 4%; BDP-MDI 168 μg BID, 2%) and oral candidiasis (4% in each treatment group). No clinically relevant changes in laboratory values, including plasma cortisol, vital signs, or physical examinations were noted in any treatment group. Conclusion Both MF-DPI doses were well tolerated, with no unusual or unexpected adverse events or safety concerns, and had a similar adverse event profile to that of BDP-MDI 168 μg BID.